On Murray Jackson's 1961 'Chair, couch and countertransference' - Connolly, Angela (Journal of analytical psychology, 2015)
One of the problems facing psychoanalysts of all schools is that theory has evolved at a much faster pace than practice. Whereas there has been an explosion of theory, practice has remained, at least officially, static and unchanging. It is in this sense that Murray Jackson's 1961 paper is still relevant today. Despite the rise of the new relational and intersubjective paradigms, most psychoanalysts, and not a few Jungian analysts, still seem to feel that the couch is an essential component of the analytical setting and process. If the use of the couch is usually justified by the argument that it favours regression, facilitates analytical reverie and protects the patient from the influence of the analyst, over time many important psychoanalysts have come to challenge this position. Increasingly these analysts suggest that the use of the couch may actually be incompatible with the newer theoretical models. This contention is strengthened by some of the findings coming from the neurosciences and infant research. This underlines the necessity of empirical research to verify the clinical effectiveness of these different positions, couch or face-to-face, but it is exactly this type of research that is lacking.